The impact of Covid-19 vaccination on the Italian healthcare system: a scenario analysis - Marcellusi, A; Fabiano, G; Sciattella, P; Andreoni, M; Mennini, FS (Springer, 2022)
Background and Objective During 2020, the only instruments for fighting against the pandemic peaks were lockdowns, physical distancing, closure of schools and non-essential businesses, and travel restrictions. The new vaccination strategy adopted in Italy in 2021 represented a new perspective for policymakers.